Comprehensive Transcriptome Sequencing of Tanaidacea with Proteomic Evidences for Their Silk. (14th December 2021) - Kakui, Keiichi; Fleming, James F; Mori, Masaru; Fujiwara, Yoshihiro; Arakawa, Kazuharu
Abstract: Tanaidaceans are small benthic crustaceans that mainly inhabit diverse marine environments, and they comprise one of the most diverse and abundant macrofaunal groups in the deep sea. Tanaidacea is one of the most thread-dependent taxa in the Crustacea, constructing tubes, spun with their silk, for shelter. In this work, we sequenced and assembled the comprehensive transcriptome of 23 tanaidaceans encompassing 14 families and 4 superfamilies of Tanaidacea, and performed silk proteomics of Zeuxo ezoensis to search for its silk genes. As a result, we identified two families of silk proteins that are conserved across the four superfamilies. The long and repetitive nature of these silk genes resembles that of other silk-producing organisms, and the two families of proteins are similar in composition to silkworm and caddisworm fibroins, respectively. Moreover, the amino acid composition of the repetitive motifs of tanaidacean silk tends to be more hydrophilic, and therefore could be a useful resource in studying their unique adaptation of silk use in a marine environment. The availability of comprehensive transcriptome data in these taxa, coupled with proteomic evidence of their silk genes, will facilitate evolutionary and ecological studies.